The Characteristics of Effective Performance Measurement System: Case Study Analysis - Stříteská Michaela; Jelínková Lucie (WSEAS Press, 2015)
Gaining a competitive advantage by achieving a certain level of business performance is the primary prerequisite for the successful operation of a company in the long term in today's highly competitive environment. For this reason, the performance measurement and management system becomes more and more important tool for evaluating of company performance. This paper deals with performance measurement systems of selected Czech companies. The main aim of the paper is to investigate the characteristics of effectively created performance measurement and management systems of monitored companies through interviews with managers and analysis of internal materials of these companies. The performance measurement systems are examined at two different levels. First the analysis of performance measurement system as an entity is carried out by exploring issues such as: multi-dimensionality of performance measures, interconnection with corporate strategy and defining performance measures at the operational level. Second the analysis of relationship between performance measurement system and environment in which it operates is performed. There is investigated whether the strategy is reformulated on the basis of performance measures evaluation and weather exist the relationship between performance measurement and reward system. The research findings are evaluated within the context of the theoretical background and the conclusions of similar studies. Based on these findings, a research field is defined and significant gaps in performance management process are formulated. The paper is elaborated on the basis of literature review and case studies analysis of selected companies.
Charakteristiky efektivního systému měření výkonnosti: analýza případových studií
Keywords: characteristics; management control; measurement; performance; system; charakteristiky; kontrolní řízení; měření; výkonnost; systém